Implementation of rules & procedures to establish student discipline in online physical education learning - Widiastuti, Widiastuti; Silvanus, Herald (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
This study aimed to describe the implementation of rules and procedures to establish student discipline in online Physical Education learning. The research method used in this study is a descriptive qualitative method with data analysis techniques including data reduction, data presentation, and conclusion drawing. The results of this study indicated that the implementation of rules and procedures in Physical Education learning can foster student discipline during online learning. Student discipline is evident as all students demonstrate discipline by activating their cameras during the class and focusing on listening to the teacher's explanation, as well as muting their microphones when not asked to speak. The majority of students also show disciplined behavior by using the "raise hand" feature when requesting permission to speak or asking questions, and they actively participate in the learning process. In conclusion, the implementation of rules and procedures successfully cultivates student discipline in online Physical Education learning. As a suggestion for future research, further studies can explore forming discipline through a personalized approach to students.